2019
DOI: 10.1080/1369183x.2019.1584705
|View full text |Cite
|
Sign up to set email alerts
|

Methodological innovations, reflections and dilemmas: the hidden sides of research with migrant young people classified as unaccompanied minors

Abstract: This paper offers some behind-the-scenes insights drawn from the collective fieldwork experiences of the contributors to this Special Issue. These include reflections on: how decisions about modes of accessing research participants fundamentally shape the research process and outcomes; the pitfalls of only focusing on young people's migratory experiences while ignoring the multiple other dimensions to their lives; how we can best capture and represent young people's often paradoxical vulnerability and agency; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 48 publications
0
38
0
Order By: Relevance
“…The highly politicised field of the border regime raises questions of research ethics concerning both non-refugees and refugees. Conducting research with vulnerabilised persons -such as young or rejected refugees -presents a unique set of conundrums, contradictions, and conflicts (Chase et al 2019). Especially when research partners find themselves in institutionalised surroundings, the question of how to approach them for research is vital.…”
Section: Methods and Analytical Frameworkmentioning
confidence: 99%
“…The highly politicised field of the border regime raises questions of research ethics concerning both non-refugees and refugees. Conducting research with vulnerabilised persons -such as young or rejected refugees -presents a unique set of conundrums, contradictions, and conflicts (Chase et al 2019). Especially when research partners find themselves in institutionalised surroundings, the question of how to approach them for research is vital.…”
Section: Methods and Analytical Frameworkmentioning
confidence: 99%
“…Some refugees may want to have a selfpresentation that conveys resilience and strength as a direct counter-reaction to that that refugees are often generally are conceived through gaze of pity, vulnerability, or charity (cf. Chase et al, 2020;Hynes, 2003;Wernesjö, 2020). Furthermore, some individuals can deem it as stigmatizing to be called a refugee, or may not wish to not be identified as a refugee because they want to "move on from their past traumas" (Stevenson & Willott, 2007, p. 684).…”
Section: Limitations Challenges and Ethicsmentioning
confidence: 99%
“…Previous studies have shown that migrants’ experiences differ widely (Björkman and Spehar, 2018) based on their expectations, journey, and the realities of the new geographical and cultural location they arrive to. As Chase et al (2019: 5) elaborate, ‘while there may be similarities in how different young people have lived through forced migration, there are likely to be as many differences’. This once again reminds us of the need to study migrants’ emotional experiences and expressions in their complexity.…”
Section: Experience and Expression Of Migratory Emotional Losses And mentioning
confidence: 99%